The natural history of pancreatic acinar cell cystadenoma: Is resection better than surveillance? An update to a case report from 2010 - David G. Darcy; Dominique Jan (Journal of Pediatric Surgery Case Reports, 2016)
Cystic lesions of the pancreas are a rare entity, and few reports have described their natural history in children. A previously published report described a 9-year-old boy with an acinar cell cystadenoma, discovered during a laparoscopic appendectomy. Initially asymptomatic and followed by serial MRI, this patient presented to our institution several years later with chronic obstructive symptoms that required surgical intervention. Planning for resection included multidisciplinary input from the genetics and endocrinology services. Initially, a partial pancreatic resection was performed in an attempt to preserve normal pancreatic tissue and islet cell function. Progression of the cystic disease and recurrent obstruction necessitated further surgical intervention. Here we present the updated clinical course and outcome of a 12-year-old boy who underwent a total pancreaticoduodenectomy for a symptomatic acinar cell cystadenoma.